2014
DOI: 10.1186/s12870-014-0293-4
|View full text |Cite
|
Sign up to set email alerts
|

HSI2/VAL1 PHD-like domain promotes H3K27 trimethylation to repress the expression of seed maturation genes and complex transgenes in Arabidopsis seedlings

Abstract: BackgroundThe novel mutant allele hsi2-4 was isolated in a genetic screen to identify Arabidopsis mutants with constitutively elevated expression of a glutathione S-transferase F8::luciferase (GSTF8::LUC) reporter gene in Arabidopsis. The hsi2-4 mutant harbors a point mutation that affects the plant homeodomain (PHD)-like domain in HIGH-LEVEL EXPRESSION OF SUGAR-INDUCIBLE GENE2 (HSI2)/VIVIPAROUS1/ABI3-LIKE1 (VAL1). In hsi2-4 seedlings, expression of this LUC transgene and certain endogenous seed-maturation gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 75 publications
1
36
0
Order By: Relevance
“…In previous reports, we showed that expression of AGL15 is strongly upregulated in both hsi2-2 knockout Arabidopsis plants and in hsi2-4 plants that carry a C-to-Y substitution in the HSI2 PHD motif (Veerappan et al, 2012). This change in expression is associated with a dramatic loss of histone 3 lysine 27 trimethylation (H3K27me3) at the AGL15 locus (Veerappan et al, 2014).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…In previous reports, we showed that expression of AGL15 is strongly upregulated in both hsi2-2 knockout Arabidopsis plants and in hsi2-4 plants that carry a C-to-Y substitution in the HSI2 PHD motif (Veerappan et al, 2012). This change in expression is associated with a dramatic loss of histone 3 lysine 27 trimethylation (H3K27me3) at the AGL15 locus (Veerappan et al, 2014).…”
Section: Introductionmentioning
confidence: 85%
“…Since expression of AGL15 is strongly upregulated and H3K27me3 enrichment is reduced in hsi2 mutants (Veerappan et al, 2012(Veerappan et al, , 2014, we hypothesize that the AGL15 locus is a direct regulatory target of HSI2. To determine if HSI2 interacts with AGL15 in vivo, an epitope-tagged HSI2-rescued Arabidopsis line was generated by the introduction of HSI2-HA coding sequence under control of the native HSI2 promoter (HSI2pro:HSI2-HA) into hsi2-2 knockout plants that contain the GSTF8pro:LUC (hsi2-2 LUC ) reporter gene (Veerappan et al, 2012(Veerappan et al, , 2014.…”
Section: Hsi2 Is Enriched At the Agl15 Promoter Regionmentioning
confidence: 93%
See 2 more Smart Citations
“…Double mutants of highlevel expression of sucrose inducible gene2 (HSI2)/VAL1 and HSI2-Like/VAL2 produce seedling expressing embryo specific genes, AFL clade genes, and accumulate high seed storage compounds. [93] Researchers recently found that a MYB and basic helix-loop-helix TFs, Transparent Testa 2 and 8 (TT2 and 8), respectively, inhibits FA biosynthesis in seed embryo by interacting with and inhibiting the FUS3 and LEC1, thereby repressing KASII and BIOTIN CARBOXYL CARRIER PROTEIN2 (BCCP2); a subunit of ACCase. [94] Arabidopsis six-b-interacting protein 1-like 1 (ASIL1) is a regulator of seed filling.…”
Section: Myb Tfs Regulate Biosynthesis Of Vlcfasmentioning
confidence: 99%